Linking Arabic, Islam, and Economy: Onomastics on Business Name of People of Arab Descent in Indonesia - Aribowo, Eric Kunto (KARSA: Journal of Social and Islamic Culture, 2017)
Name has a great influence in building the success of a business. The business strategy of people of Arab descent is to use Arabic words rather than English words to build the image of his shop. This paper explores how the use of Arabic words and strategic reasons of Arab descendants in Pasar Kliwon, Surakarta designates as the name of his shop. The data were taken by observing and taking pictures of store names from promotional media: store board, banner, and neon box followed by interviews with 10 shopkeepers. The data are then analyzed by classify the store names from the writing system and tracing the reference words used. The results show that business names are more dominated by single Arabic words; a small portion is an Arab-English combination. The bussiness names are derived from the proper name, surname, and places that have an Islamic nuance. This activity aims to build a positive image in the minds of consumers, showing the identity of who the owners and commodities, as well as convince consumers of halal products.Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i2.1390